Molecular phylogeny and systematic evaluation of the Caragana opulens species complex (Fabaceae, Papilionoideae) based on the molecular and morphological data - Rather, Shabir A.; Shu, Wang; Dwivedi, Mayank Dhar; Zhaoyang, Chang (Phytotaxa, 2021)
In this study, we explored the evolutionary history and taxonomic treatment of the Caragana opulens complex taking information from morphological and molecular data. The complex consists of three species, C. opulens, C. licentiana and C. kansuensis. Moreover, the morphological characters currently used to differentiate the species present in the complex have been found insignificant and inconsistent and do not help diagnose the species. For the present study, we investigated its range and sampled 139 accessions from the different populations of the genus Caragana and 17 accessions of the complex. DNA sequence data from one nrDNA ITS and one cpDNA trnH-psbA loci were sequenced and analyzed using Maximum Likelihood and Bayesian methods. The resulting phylogenies were congruent in topologies. Based on morphological and molecular data, it is concluded that all three species of the complex are one of the same with significant morphological variations. Hence C. opulens is accepted as the correct name along with C. licentiana and C. kansuensis as synonyms.